1989
DOI: 10.1136/bjo.73.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Epiblepharon with inverted eyelashes in Japanese children. I. Incidence and symptoms.

Abstract: SUMMARY Epiblepharon commonly occurs in Japanese infants and tends to disappear spontaneously with age. We examined 4449 Japanese children aged 3 months to 18 years for epiblepharon associated with inverted eyelashes touching the cornea. The condition was evident in 441 cases. We found that the incidence of epiblepharon decreased with age, but about 2% of high school students still had the condition. No sexual predilection was found. Lower eyelids were commonly involved bilaterally. Most cases of epiblepharon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
9

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 1 publication
3
67
9
Order By: Relevance
“…The high body mass index (overweight and obesity) was associated with epiblepharon in pediatric patients with nephrotic syndrome. The prevalence of epiblepharon in children with nephrotic syndrome was higher than that in Japanese school children, as reported previously by us [11, 16]. Carter et al [17] reported that orbital fat projected further anteriorly with respect to the orbital rim in the lower eyelid in all Asians.…”
Section: Discussionsupporting
confidence: 62%
“…The high body mass index (overweight and obesity) was associated with epiblepharon in pediatric patients with nephrotic syndrome. The prevalence of epiblepharon in children with nephrotic syndrome was higher than that in Japanese school children, as reported previously by us [11, 16]. Carter et al [17] reported that orbital fat projected further anteriorly with respect to the orbital rim in the lower eyelid in all Asians.…”
Section: Discussionsupporting
confidence: 62%
“…Second, the incidence of epiblepharon in non-DS Asian children, decreases with age, and only 4.2% showed epiblepharon after 7 years of age. 18 In contrast, the incidence of epiblepharon did not decrease with age much among the patients with DS, and 53% of the patients after 7 years of age still showed epiblepharon. Third, photophobia or epiphora, a common symptom of epiblepharon, was noticed much less commonly in DS children with multiple corneal punctate epithelial erosions than non-DS Asian children in the same situation.…”
Section: Discussionmentioning
confidence: 81%
“…First, in non-DS Asian children with epiblepharon, the medial part of the lower eyelid was most commonly involved, and the upper eyelid, the least commonly involved. 18 However, in the epiblepharon with DS, the upper eyelid was characteristically most commonly involved. Second, the incidence of epiblepharon in non-DS Asian children, decreases with age, and only 4.2% showed epiblepharon after 7 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Also, entropion was not described in children in other studies, except that of Wada et al Entropion is not due to thyrotoxicosis but to secondary anatomical abnormalities. Epiblepharon commonly occurs in Japanese infants; 4449 Japanese children were examined for epiblepharon associated with inverted eyelashes and 441 cases of this condition were observed [15]. Therefore, Japanese infants with Graves' disease, including our case, might show a tendency to have entropion due to epiblepharon as well as lower lid retraction.…”
Section: Discussionmentioning
confidence: 99%